PENERAPAN TEKNIK CHUNKING DIPADU WRITING IS THINKING UNTUK MENGENDALIKAN BEBAN KOGNITIF DAN PENGARUHNYA TERHADAP LEVEL BERPIKIR SISWA SMA PADA PEMBELAJARAN SISTEM REPRODUKSI MANUSIA - Meirin Dwiningtyas Putri, - (2023)
The use of learning strategies has an important role in controlling cognitive load and its effect on students' thinking levels. This study aims to control cognitive load and increase students' thinking levels in learning the human reproductive system using chunking techniques combined with writing is thinking. The research method that has been used is a quasi-experimental with a pretest and posttest design. The subjects of this research were students of class XI MIPA at one of Senior High Schools Tasikmalaya City using a purposive sampling technique involving 56 students consisted of 28 experimental group students and 28 control group students. Chunking technique is carried out by the teacher by dividing material into sub-material and sub-material into material concepts. Writing is thinking is done by students by rewriting the concept of material that has been obtained in their own words or language to make it easier to understand. Cognitive load was measured using a subjective rating scale questionnaire instrument with a Likert scale from 1 to 8. Thinking level was measured using multiple choice and essay questions. The results of the research show that students whose learning process uses chunking techniques combined with writing is thinking obtain a low Intrinsic Cognitive Load (ICL), a low Extraneous Cognitive Load (ECL) and a high Germane Cognitive Load (GCL) which has an impact on students' thinking levels, especially level 4 (knowledge utilization). The application of the chunking technique combined with writing is thinking can controlled cognitive load, but controlled cognitive load is not only factor that increase the level of thinking. Keywords: cognitive load, thinking level, human reproductive system, chunking technique, writing is thinking